Nonlinear Seismic Performance Evaluation of Flexural Slotted Connection Using Endurance Time Method - Seyed Mohamad Seyed Kolbadi; Hosein Piri; Ali Keyhani; S.Mahdi Seyed-Kolbadi; Masoud Mirtaheri (Shock and Vibration)
The equivalent statistical methods, spectral analysis, and time history analysis are usually offered in the steel structure design regulations. Among these methods, the third one is more accurate; however, it requires more time to align the accelerometers due to a large number of analyses. In the endurance time (ET) method, incremental acceleration functions gradually and uniformly increases over time while their linear and nonlinear response spectra are proportional to the mean of the real seismic spectrum. These functions are used as input functions to analyze the nonlinear time history of structures, and the performance of structures is evaluated based on the maximum length of time they can meet specified performance goals. A three-story steel bending frame with (slotted web) SW and (web unslotted flange) WUF connection is examined through the performance time method in performance-based design. This article aimed at evaluating the seismic performance of these connections in the bending frame through endurance time analysis to predict the structural response in the probabilistic evaluation of the seismic performance of the structures. It is found that the endurance time analysis is justified with the seismic performance of the connections with low computational cost and proper accuracy. The results of comparing both SW and WUF connections indicated that the SW connection prevents the connection welding area from being failed due to transferring the plastic joint into the beam and in an area away from the column face and causes less damage compared to the WUF connection.